Teaching's orderline of a pupil with rare disease by a support teacher - Agnieszka Kamyk-Wawryszuk (Kazimierz Wielki University, 2017)
The present article concerns a teaching's orderlie of of a pupil with rare disease in the inclusive ward of mass educational school. The dimension of support teacher's job have been discribed, especially activities - which should be done by a teacher to help a pupil to absorb knowledge - so have been kinds of work, which should be applied in order to assist mentioned process.